PERMIAN STRATIGRAPHY AND CORRELATION OF NORTHEAST CHINA: A REVIEW - Shen S.Z.; Zhang H.; Li W.Z.; Shang Q.H. (My University, 2006)
Palaeontological, lithostratigraphical data from the Permian strata and correlation of the Permian successions for different tectonic units in Northeast China are reviewed and summarized in this paper. Permian strata in Northeast China are dominated by brachiopods, fusulinoideans and land plants, with limited ammonoids, conodonts and bivalves. The Cisuralian (Early Permian) in the northern margin of the North China Block and in the Manchuride Belt is composed mostly of marine massive limestone with the characteristic Pseudoschwagerina Zone in the Asselian and Sakmarian and the Misellina claudiae Zone in the Kungurian. The Cisuralian in the Xing'an Block and the northeastern part of Inner Mongolia is dominated by huge terrestrial deposits with fossil plants. The Guadalupian (Middle Permian) in the Manchuride, Altaid and Yanbian Belts are characterized by bi-temperate Roadian or early Wordian Monodiexodina fauna and the late Wordian-Capitanian Codonofusiella-Schwagerina or Neoschwagerina-Yabeina faunas, the mixed brachiopod faunas between the Boreal/antitropical and the Palaeoequatorial Cathaysian forms, the Roadian or early Wordian solitary coral faunas, and the late Wordian-Capitanian compound Waagenophyllum-Wentzelella fauna. The Nadanhada Terrane contains some exotic limestone blocks with a typical Cathaysian Neoschwagerina-Yabeina fauna in a Late Jurassic-Early Cretaceous mélange, which is related to Mesozoic subduction in the western Circum-Pacific region. The Lopingian (Late Permian) in Northeast China is mostly characterized by terrestrial molasse deposits with a mixed flora between the Boreal Angaran and the palaeoequatorial Cathaysian Provinces, indicating the final closure of the Palaeo-Asian Ocean. © 2005 Elsevier Ltd. All rights reserved.
Keywords: CORRELATION; NORTHEAST CHINA; PERMIAN; STRATIGRAPHY; Paleozoic::Permian; Палеозой::Пермская